Genome-edited, donor-derived allogeneic anti-CD19 chimeric antigen receptor T cells in paediatric and adult B-cell acute lymphoblastic leukaemia: results of two phase 1 studies. Issue 10266 (12th December 2020) - Benjamin, Reuben; Graham, Charlotte; Yallop, Deborah; Jozwik, Agnieszka; Mirci-Danicar, Oana C; Lucchini, Giovanna; Pinner, Danielle; Jain, Nitin; Kantarjian, Hagop; Boissel, Nicolas; Maus, Marcela V; Frigault, Matthew J; et al.
Summary: Background: Genome-edited donor-derived allogeneic anti-CD19 chimeric antigen receptor (CAR) T cells offer a novel form of CAR-T-cell product that is available for immediate clinical use, thereby broadening access and applicability. UCART19 is one such product investigated in children and adults with relapsed or refractory B-cell acute lymphoblastic leukaemia. Two multicentre phase 1 studies aimed to investigate the feasibility, safety, and antileukaemic activity of UCART19 in children and adults with relapsed or refractory B-cell acute lymphoblastic leukaemia. Methods: We enrolled paediatric or adult patients in two ongoing, multicentre, phase 1 clinical trials to evaluate the safety and antileukaemic activity of UCART19. All patients underwent lymphodepletion with fludarabine and cyclophosphamide with or without alemtuzumab, then children received UCART19 at 1·1–2·3 × 10 6 cells per kg and adults received UCART19 doses of 6 × 10 6 cells, 6–8 × 10 7 cells, or 1·8–2·4 × 10 8 cells in a dose-escalation study. The primary outcome measure was adverse events in the period between first infusion and data cutoff. These studies were registered at ClinicalTrials.gov, NCT02808442 and NCT02746952. Findings: Between June 3, 2016, and Oct 23, 2018, seven children and 14 adults were enrolled in the two studies and received UCART19. Cytokine release syndrome was the most common adverse event and was observed in 19 patients (91%); three (14%) had grade 3–4 cytokine release syndrome. Other adverse events were grade 1 or 2 neurotoxicity in eight patients (38%), grade 1 acute skin graft-versus-host disease in two patients (10%), and grade 4 prolonged cytopenia in six patients (32%). Two treatment-related deaths occurred; one caused by neutropenic sepsis in a patient with concurrent cytokine release syndrome and one from pulmonary haemorrhage in a patient with persistent cytopenia. 14 (67%) of 21 patients had a complete response or complete response with incomplete haematological recovery 28 days after infusion. Patients not receiving alemtuzumab (n=4) showed no UCART19 expansion or antileukaemic activity. The median duration of response was 4·1 months with ten (71%) of 14 responders proceeding to a subsequent allogeneic stem-cell transplant. Progression-free survival at 6 months was 27%, and overall survival was 55%. Interpretation: These two studies show, for the first time, the feasibility of using allogeneic, genome-edited CAR T cells to treat patients with aggressive leukaemia. UCART19 exhibited in-vivo expansion and antileukaemic activity with a manageable safety profile in heavily pretreated paediatric and adult patients with relapsed or refractory B-cell acute lymphoblastic leukaemia. The results this study are an encouraging step forward for the field of allogeneic CAR T cells, and UCART19 offers the opportunity to treat patients with rapidly progressive disease and where autologous CAR-T-cell therapy is unavailable. Funding: Servier.